Hematological and biochemical alterations in preeclampsia: Readings from cord blood analysis - Ahmed Abu Siniyeh; Mohammad Alsahoury; Talal Al Qaisi; Majed Al-Holi (PLoS ONE, 2025)
Background Preeclampsia is a serious complication of pregnancy characterized by hypertension and proteinuria that adversely affects both maternal and fetal health. This study aimed to investigate hematological and biochemical alterations in cord blood associated with preeclampsia, with a focus on hemoglobin variants and blood gas parameters. Methods A case‒control study involving 54 participants, including 24 women diagnosed with preeclampsia and 30 normotensive controls, was conducted. Cord blood samples were analyzed for total hemoglobin (Hb), blood gas, and complete blood count (CBC) indices. Statistical analyses included independent t tests for parametric data and Mann‒Whitney U tests for nonparametric data, with significance set at p < 0.05. Results The results revealed significant differences in hemoglobin concentrations, with cord blood collected from preeclamptic women exhibiting lower levels of adult hemoglobin (HbA) (64.0% ± 32.0% vs. 76.2% ± 25.7%, p = 0.004) and higher fetal hemoglobin (HbF) concentrations (35.9% ± 32.1% vs. 23.7% ± 25.6%, p = 0.004) than controls. Blood gas parameters, including pH and bicarbonate and carbon dioxide levels, were not significantly different between the groups. However, CBC results revealed a lower platelet count in the cord blood of the preeclamptic group than in the cord blood of the preeclampsia group, (213.7*103/µL ± 112*103/µL vs. 314.6*103/µL ± 70.8*103/µL, p = 0.0005). Conclusions While our study reveals significant alterations in fetal hemoglobin variants and CBC indices in the cord blood of preeclamptic pregnancies, the clinical applicability of these markers for early detection is currently limited by the inaccessibility of fetal blood before delivery. Nevertheless, these findings offer important insights into the hematological changes linked to preeclampsia. Future studies should explore the potential of detecting similar alterations in maternal blood as a more feasible and non-invasive approach for early diagnosis and risk assessment of preeclampsia.